A 16-QAM 100-Gb/s 1-M Wireless Link With an EVM of 17% at 230 GHz in an SiGe Technology - Rodriguez-Vazquez, Pedro; Grzyb, Janusz; Heinemann, Bernd; Pfeiffer, Ullrich R. (IEEE microwave and wireless components letters, 2019)
This letter presents a 1-m wireless link established with a set of fundamentally operated Tx/Rx direct-conversion in-phase and quadrature (IQ) radio frequency (RF) front-end modules in a 0.13-μm SiGe HBT technology featuring full chipon-board packaging. Using a 16-quadrature amplitude modulation, data rates from 20 to 100 Gb/s with an error vector magnitude from 7% to 17% were achieved at a 1-m distance. Thanks to the new mixer-first Rx, the maximum data rate improved from 90 to 100 Gb/s compared with our previous work using the amplifier-first Rx. The peak performance was reached at 230 GHz. The Tx operates at a 3.5 dB backoff from Psat showing a 3-dB RF bandwidth (BW) of 28 GHz, a Pout of 5 dBm, and an IQ imbalance below 0.7 dB. The Rx features a peak conversion gain of 8 dB, a single-sideband noise figure of 14 dB, a 3-dB RF BW of 26 GHz, and an IQ imbalance below 1 dB. This letter also provides an analysis of the RF front-end imperfections related to the large link BW.